2016
DOI: 10.3758/s13414-016-1168-6
|View full text |Cite
|
Sign up to set email alerts
|

The control of attentional target selection in a colour/colour conjunction task

Abstract: To investigate the time course of attentional object selection processes in visual search tasks where targets are defined by a combination of features from the same dimension, we measured the N2pc component as an electrophysiological marker of attentional object selection during colour/ colour conjunction search. In Experiment 1, participants searched for targets defined by a combination of two colours, while ignoring distractor objects that matched only one of these colours. Reliable N2pc components were trig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
3
6
0
Order By: Relevance
“…Until 250 ms after search display onset, attentional guidance was found to be entirely feature-based, and objectbased control started to affect visual processing only after this point in time. This is in line with observations from previous N2pc studies of conjunction search (Berggren & Eimer, 2016a;Eimer & Grubert, 2014;Jenkins et al, 2017;Nako et al, 2016), which found that target N2pc amplitudes were initially equal in size to the sum of N2pcs to partially matching nontargets, but became larger (i.e., superadditive) around 250 ms after search display onset. The design of these earlier experiments made it impossible to decide whether the emergence of a superadditive N2pc reflected object-based attentional control or local facilitatory interactions between feature-specific attentional biases.…”
Section: Discussionsupporting
confidence: 92%
“…Until 250 ms after search display onset, attentional guidance was found to be entirely feature-based, and objectbased control started to affect visual processing only after this point in time. This is in line with observations from previous N2pc studies of conjunction search (Berggren & Eimer, 2016a;Eimer & Grubert, 2014;Jenkins et al, 2017;Nako et al, 2016), which found that target N2pc amplitudes were initially equal in size to the sum of N2pcs to partially matching nontargets, but became larger (i.e., superadditive) around 250 ms after search display onset. The design of these earlier experiments made it impossible to decide whether the emergence of a superadditive N2pc reflected object-based attentional control or local facilitatory interactions between feature-specific attentional biases.…”
Section: Discussionsupporting
confidence: 92%
“…Because targets were defined by a combination of two shapes, these results also provide further evidence that search can be controlled by templates for multiple features from the same dimension. This is in line with the conclusion drawn in previous studies of color/color conjunction search (Berggren & Eimer, 2016a; Grubert & Eimer, 2016; Irons et al, 2012), but inconsistent with the hypothesis of the Guided Search model that only a single feature per dimension can be involved in attentional guidance (Wolfe, 2007).…”
Section: Discussionsupporting
confidence: 73%
“…Using behavioral measures, Irons, Folk, and Remington (2012) showed that during search for one of two possible target colors (e.g., red or green objects), task-irrelevant stimuli that matched either of these colors captured attention, whereas nonmatching colors did not (see also Grubert & Eimer, 2016, for corresponding N2pc results). To assess how such multiple-color templates control attentional target selection in search tasks where targets are defined by a combination of two colors (e.g., red and green objects), Berggren and Eimer (2016a) measured N2pc components to target objects with both two target-defining colors and to distractors that matched one of these colors. Reliable N2pc components were elicited not only by targets but also by partially matching distractor objects, even when a target was simultaneously present in the same display.…”
mentioning
confidence: 99%
“…There is also electrophysiological evidence for some color-based attention becoming effective within 100 ms of stimulus onset (Zhang & Luck, 2009). Other studies show signs of guidance that appear at about 250 ms (e.g., Berggren & Eimer, 2016). It is possible that the full implementation of guidance requires feedback from high cortical areas, as proposed in models like the Reverse Hierarchy Theory of Ahissar and Hochstein (Ahissar & Hochstein, 2004;Hochstein & Ahissar, 2002) or the reentrant account of Di Lollo et al (2000).…”
Section: Discussionmentioning
confidence: 97%